Traumatic Brain Injury (TBI) and Concentrated EMDR: A case study - Yaşar, Alişan Burak; Altunbaş, Fatma Dilara; Picard, Inci Tebis; Gündüz, Anıl; Konuk, Emre; Kavakçı, Önder (Klinik Psikiyatri Dergisi, 2022)
It has been highlighted that comorbidity of Traumatic Brain Injury (TBI) and PTSD leads a more complicated treatment process. Hence, it might be useful and practical to provide more trauma-focused therapy methods such as eye movement desensitization and reprocessing (EMDR) therapy. This article illustrates a clinical case by describing the positive outcome of the concentrated EMDR therapy with a treatment frequency increased more than one session in a week of a 25 year old woman with TBI and PTSD. EMDR treatment has been provided for ten days and seven sessions in total for 90 min in each session. The results of the treatment have been measured with CAPS, SUD and VOC score. Results show the effectiveness of concentrated EMDR even after the 16 month follow up.
Travmatik Beyin Hasarı ve Konsantre EMDR: Olgu sunumu
Keywords: Traumatic Brain Injury (TBI); Eye Movement Desensitization and Reprocessing (EMDR); Concentrated EMDR